Triassic magmatism and tectonic setting of Eastern Tianshan, NW China: constraints from the geochemistry and zircon U–Pb–Hf isotopes of granitoids in the Yamansu area - Cai, Hongming; Gong, Xiangkuan; Liu, Guiping; Guo, Ruiqing; Wang, Keyong (Frontiers in Earth Science, 2023)
Introduction: To provide constraints on the Triassic tectonic setting of Eastern Tianshan, an integrated study was conducted on the geochronological and geochemical data for granodiorites, monzogranites, and two-mica granites from the Yamansu area on the northern margin of the Central Tianshan, NW China. Geochronlogy Method and Results: Zircon U–Pb dating indicated the crystallization ages of ca. 250–241 Ma. Geochemistry Results: The granodiorites (ca. 250 Ma) were medium-K calc-alkaline I-type granitoids, with crust-derived geochemical elements ratios (e.g., Ti/Zr, Ti/Y, and Nb/Ta), low Sr/Y ratios, and moderate negative Eu anomalies (Eu/Eu* = 0.56–0.57), suggesting their derivation from the partial melting of crustal materials with plagioclase as a major residual phase at <12 kbar. The monzogranites (ca. 247 Ma) showed adakitic characteristics, with high SiO2 and low MgO, Cr, and Ni contents and low Nb/Ta ratios, indicating an origin from the melting of thickened mafic lower crusts at relatively high pressure (12–15 kbar). The ca. 244 Ma and ca. 241 Ma two-mica granites were high-K calc-alkaline and showed geochemical features of highly fractionated I-type granites. They were generated by melting medium-to-high-K mafic to intermediate crustal rocks at pressures <5 kbar, accompanied mainly by feldspar fractional crystallization. All granitoids had zircon εHf(t) values of +7.8 to +2.1, with corresponding TDM2 of 1132–773 Ma, suggesting juvenile crustal rocks as possible sources. Discussion: Geochronological investigations of the studied granitoids, together with published data, suggest that the Triassic was an important period for granitic magmatism in Eastern Tianshan. Considering all the available geological data, we suggest that the Triassic granitoids were formed in an intracontinental environment possibly controlled mainly by far-field effects of the Paleo-Tethys system, with contemporaneous compression and extension at deep and shallower lithosphere depths, respectively, during the Triassic.